2001
DOI: 10.4319/lo.2001.46.6.1392
|View full text |Cite
|
Sign up to set email alerts
|

Physiological constraints on bromoform (CHBr3) production by Ulva lactuca (Chlorophyta)

Abstract: Physiological factors affecting bromoform (CHBr 3 ) production by Ulva lactuca were investigated using metabolic inhibitors and presumed substrates of bromoperoxidase (BrPO). The metabolic inhibitors were used at a verified physiologically active concentration. Bromoform production was nearly tripled in the light (376 Ϯ 92 pg cm Ϫ2 h Ϫ1 ) compared to the dark (114 Ϯ 70 pg cm Ϫ2 h Ϫ1 ), was inhibited in the light in the presence of the photosynthetic inhibitor DCMU, and was inhibited in the dark in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 30 publications
1
46
0
Order By: Relevance
“…It would be unlikely that 1‐butene is not photochemically produced, but these results suggest that future studies of 1‐butene production from terrestrial plants may be worthwhile. Bromoform is known to be emitted from several macroalgea [ Carpenter and Liss , 2000; Manley and Barbero , 2001] although emissions by terrestrial plants have not yet been observed. Seasonally integrated bromoform emissions in planted chambers (0.025 ± 0.013 mg m −2 ) were higher than those from control chambers (0.014 mg m −2 ), but not significantly so.…”
Section: Resultsmentioning
confidence: 99%
“…It would be unlikely that 1‐butene is not photochemically produced, but these results suggest that future studies of 1‐butene production from terrestrial plants may be worthwhile. Bromoform is known to be emitted from several macroalgea [ Carpenter and Liss , 2000; Manley and Barbero , 2001] although emissions by terrestrial plants have not yet been observed. Seasonally integrated bromoform emissions in planted chambers (0.025 ± 0.013 mg m −2 ) were higher than those from control chambers (0.014 mg m −2 ), but not significantly so.…”
Section: Resultsmentioning
confidence: 99%
“…Current evidence suggests that marine CHBr 3 , CH 2 Br 2 , and CHClBr 2 are primarily produced naturally, such as by macroalgae, ice algae and phytoplankton [e.g., Carpenter and Liss , 2000; Gschwend and MacFarlane , 1986; Manley and Barbero , 2001; Manley et al , 1992; Moore et al , 1996; Sturges et al , 1992, 1993; Tokarczyk and Moore , 1994]. CHBr 3 and CHClBr 2 also have anthropogenic sources as by‐products of water disinfection [e.g., Nieuwenhuijsen et al , 2000; Quack and Wallace , 2003; Ram et al , 1990].…”
Section: Introductionmentioning
confidence: 99%
“…Whether the evolved volatile iodine species produced by marine algae have a biological function is currently unknown. They may simply be a by-product of the intra-and intercellular removal of the H 2 O 2 from algal tissue (Manley and Barbero, 2001), alternatively they may also act to deter the grazing of zooplankton. These biological phenomena have, however, significant impacts on atmospheric chemistry on scales from the local and global (see Section Reactive Iodine Species in the Atmosphere).…”
Section: Iodine From Marine Algae and Microbesmentioning
confidence: 99%